A composite lithium metal negative electrode carrier material and preparation method thereof and lithium-sulfur battery

By using graphite oxide and bacterial cellulose as carrier materials in the negative electrode of lithium sulfur battery and adding Co(PO3)2, the problems of lithium dendrites growth and lithium volume expansion are solved, and the stability of lithium sulfur battery negative electrode is significantly improved and Cyclic performance.

CN119240626BActive Publication Date: 2025-02-25SOUTHWEST PETROLEUM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411764524.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The negative electrode of lithium sulfur battery has problems such as uncontrollable growth of lithium dendrites, volume expansion during the deposition/stripping of lithium, and side reactions between lithium polysulfide, resulting in unstable SEI of the negative electrode, rapid capacity decay, and poor cycle stability. and safety hazards.

Method used

Using graphite oxide and bacterial cellulose as carrier materials, the composite lithium metal negative electrode carrier material is prepared through specific mass ratios and treatment steps, and Co(PO3)2 is added to provide lithium-philic sites, inhibit the growth of lithium dendrites and improve the negative electrode. stability.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, improve the stability of the negative electrode of lithium sulfur battery, reduce the volume expansion of lithium, and improve the cycle stability and safety of lithium sulfur battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240626B_ABST
    Figure CN119240626B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and in particular to a composite lithium metal negative electrode carrier material and a preparation method thereof and a lithium-sulfur battery. The preparation method comprises the following steps: dispersing graphite oxide and bacterial cellulose respectively to obtain a graphite oxide dispersion and a bacterial cellulose dispersion, mixing the two to obtain a gel, wherein the mass ratio of graphite oxide to bacterial cellulose is 38-58:0.8-3.8; adding phytic acid to the gel, and then adding a hexahydrated cobalt nitrate solution thereto to react to obtain a precursor solution, wherein the mass ratio of phytic acid to graphite oxide is 580-585:38-58, and the mass ratio of cobalt nitrate hexahydrate to graphite oxide is 71-75:38-58; freeze-drying the precursor solution to obtain an intermediate; and calcining the intermediate in an inert gas atmosphere at 280-310°C for 25-35min and then at 880-930°C for 1.8-2.2h to obtain a composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite lithium metal negative electrode carrier material and a preparation method thereof, and a lithium-sulfur battery. Background Art

[0002] Lithium-sulfur batteries have a high theoretical energy density (2600 Wh kg -1 ), the cathode material is rich in reserves, cheap, non-toxic and easy to recycle, and is one of the most promising energy storage systems. After decades of development, significant breakthroughs have been made in the conductivity, volume expansion and polysulfide shuttling of lithium-sulfur battery cathode materials. However, the uncontrollable growth of dendrites in the lithium negative electrode, the volume expansion during the deposition / stripping of lithium, and the side reactions between lithium and lithium polysulfide will still cause the instability of the negative electrode SEI of lithium-sulfur batteries, rapid capacity decay, poor cycle stability and safety hazards, which is also a key factor restricting the commercial development of lithium-sulfur batteries.

[0003] In recent years, researchers have improved the electrochemical properties of lithium-sulfur batteries from the perspective of lithium metal anodes, such as using lithium-philic three-dimensional porous materials as lithium carriers to construct composite lithium anodes, thereby limiting the volume expansion of lithium metal during charging and discharging, uniformizing the local current density on the negative electrode surface, and inhibiting the tip effect, thereby stabilizing the SEI film and inhibiting the growth of lithium dendrites. Summarizing literature reports, it is found that lithium-philic carrier materials must have the following characteristics: ① High conductivity to ensure rapid transmission of electrons in the negative electrode and reduce battery resistance; ② Porous structure to promote rapid transmission of electrolytes, while providing sufficient space for the deposition and stripping of lithium, alleviating the volume change of lithium metal during charging and discharging; ③ Uniform lithium-philic sites to guide the uniform deposition of lithium ions and avoid the formation of lithium dendrites. Therefore, the careful design and preparation of three-dimensional porous lithium carrier materials with the above key characteristics can significantly improve the negative electrode performance of lithium-sulfur batteries. Summary of the invention

[0004] In view of the above-mentioned problems existing in the negative electrode of the existing lithium-sulfur battery, the present invention provides a method for preparing a composite lithium metal negative electrode carrier material. The prepared composite lithium metal negative electrode carrier material can effectively inhibit the growth of negative electrode lithium dendrites and has broad application prospects for improving the stability of the negative electrode of the lithium-sulfur battery.

[0005] In a first aspect, the present invention provides a method for preparing a composite lithium metal negative electrode carrier material, comprising the following steps:

[0006] Dispersing graphite oxide and bacterial cellulose respectively to obtain graphite oxide dispersion and bacterial cellulose dispersion, mixing the two to obtain a gel, wherein the mass ratio of graphite oxide to bacterial cellulose is 38-58:0.8-3.8;

[0007] After adding phytic acid to the gel, a cobalt nitrate hexahydrate solution is added thereto to react and obtain a precursor solution, wherein the mass ratio of phytic acid to graphite oxide is 580-585:38-58, and the mass ratio of cobalt nitrate hexahydrate to graphite oxide is 71-75:38-58;

[0008] freeze-drying the precursor solution to obtain an intermediate;

[0009] The intermediate was first calcined at 280-310°C for 25-35 min and then calcined at 880-930°C for 1.8-2.2 h in an inert gas atmosphere to obtain a PC@Co(PO3)2 composite material.

[0010] As a possible design, the mass ratio of the graphite oxide to the bacterial cellulose is 51.2:1.8; the mass ratio of the phytic acid to the graphite oxide is preferably 580:51.2; and the mass ratio of the cobalt nitrate hexahydrate to the graphite oxide is preferably 73:51.2.

[0011] As a possible design, the freeze-drying temperature is -40°C to -50°C.

[0012] As a possible design, the inert gas is argon.

[0013] As a possible design, the intermediate was first calcined at 300°C for 30 min and then at 900°C for 2 h in an inert gas atmosphere to obtain a PC@Co(PO3)2 composite material.

[0014] As a possible design, the density of graphite oxide in the graphite oxide dispersion is 6.0-7.0 mg / mL; the mass percentage of bacterial fiber in the bacterial cellulose dispersion is 75-85%.

[0015] As a possible design, the intermediate is coated with copper foil and then calcined.

[0016] In a second aspect, the present invention provides a lithium-sulfur battery, wherein the negative electrode material of the lithium-sulfur battery is mainly made of the aforementioned composite lithium metal negative electrode carrier material, a binder and a conductive agent.

[0017] As a possible design, the negative electrode material is coated on a copper foil to form a negative electrode sheet, and the coating thickness of the negative electrode material on the copper foil is 45-55 μm.

[0018] Beneficial effects of the present invention:

[0019] The composite lithium metal negative electrode carrier material prepared by the present invention contains Co(PO3)2, which has a lithium-philic property and provides more active site positions for lithium ions, thereby guiding the uniform deposition of the lithium negative electrode, inhibiting the uncontrollable growth of lithium dendrites, and improving the stability of the lithium metal negative electrode of the lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a coulombic efficiency diagram of a Li / / Cu half-cell assembled by pairing the negative electrode with lithium in Example 1, Example 2, Example 3, Example 4 and Comparative Example 5 of the present application;

[0021] Figure 2 It is a capacity-voltage diagram of a Li / / Cu half-cell assembled by pairing a negative electrode with lithium in Example 1, Example 2, Example 3, Example 4 and Comparative Example 5 of the present application;

[0022] Figure 3 It is a coulombic efficiency diagram of Li / / Cu half-cells assembled by pairing the negative electrode with lithium in Example 3, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 of the present application;

[0023] Figure 4 It is a time-voltage curve of the Li / / Li symmetric battery assembled with materials in Example 3 and Comparative Example 5 of the present application; wherein Figure 4 Figure a shows the temperature at 3 mA·cm -2 The time-voltage curve of the Li / / Li symmetric battery assembled with the negative electrode in Example 3 and Comparative Example 5 when cycled at the current density is shown in FIG. Figure 4 Figure b is a partial enlarged view of the battery time-voltage curve with the horizontal axis between 59.5h and 66.5h in Figure a;

[0024] Figure 5 It is the XRD spectrum of the material in Example 3 and the XRD spectrum of the material in Comparative Examples 1-4 in the present application; Figure 5 Figure a shows the XRD spectra of the material in Example 3 and Co(PO3)2 when the test range is 10° to 80°. Figure 5 Figure b is the XRD spectrum of the carrier material of Comparative Examples 1-4;

[0025] Figure 6 These are SEM images of the material in Example 3 of the present application at different magnifications; wherein, Figure a is a SEM image at 5µm, Figure b is a SEM image at 2µm, and Figure c is a SEM image at 1µm. DETAILED DESCRIPTION

[0026] Example 1

[0027] This embodiment discloses a method for preparing a composite lithium metal negative electrode carrier material, which specifically includes the following steps:

[0028] (1) Take 38.4 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; 3.5 mg of bacterial cellulose is dispersed in deionized water to form a bacterial cellulose dispersion with a mass percentage of 80%; the graphite oxide dispersion and the bacterial cellulose dispersion are mixed evenly to form a gel; 0.58 g of phytic acid is added to the gel; finally, 73 mg of Co(NO3)2 is added to the mixed solution and fully dissolved and shaken to obtain a precursor solution.

[0029] (2) The precursor solution is transferred to liquid nitrogen for pre-freezing until the sample is completely frozen and then placed in a freeze dryer for 24 h to 36 h. The freeze drying temperature is -40°C to -45°C, so that the sample is completely dried to obtain the intermediate.

[0030] (3) The intermediate was transferred to a tubular furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating. The resulting sample was labeled PC@Co(PO3)2-1.

[0031] (4) PC@Co(PO3)2-1, acetylene black and polyvinylidene fluoride (PVDF) were mixed and ground in a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) was added in an appropriate amount during the grinding process until it was ground into a uniform slurry. The slurry was scraped onto copper foil with a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-1 electrode.

[0032] Example 2

[0033] (1) Take 44.8 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; disperse 2.6 mg of bacterial cellulose in deionized water to form a bacterial cellulose dispersion with a mass percentage of 80%; mix the graphite oxide dispersion and the bacterial cellulose dispersion to form a gel; add 0.58 g of phytic acid to the gel; finally, add 73 mg of Co(NO3)2 to the mixed solution and fully dissolve and shake to obtain a precursor solution.

[0034] (2) The precursor solution is transferred to liquid nitrogen for pre-freezing until the sample is completely frozen and then placed in a freeze dryer for drying for 24 h to 36 h. The freeze drying temperature is -48 °C to -50 °C, so that the sample is completely dried to obtain the intermediate.

[0035] (3) The intermediate was transferred to a tubular furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating treatment. The obtained sample was labeled PC@Co(PO3)2-2.

[0036] (4) PC@Co(PO3)2-2, acetylene black and PVDF were mixed and ground in a mass ratio of 8:1:1. NMP was added in an appropriate amount during the grinding process until it was ground into a uniform slurry. The slurry was scraped onto copper foil using a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-2 electrode.

[0037] Example 3

[0038] (1) Take 51.2 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; 1.8 mg of bacterial cellulose is dispersed in deionized water to form a bacterial cellulose dispersion with a mass percentage of 80%; the graphite oxide dispersion and the bacterial cellulose dispersion are mixed evenly to form a gel; 0.58 g of phytic acid is added to the gel; finally, 73 mg of Co(NO3)2 is added to the mixed solution and fully dissolved and shaken to obtain a precursor solution.

[0039] (2) The precursor solution is transferred to liquid nitrogen for pre-freezing until the sample is completely frozen and then placed in a freeze dryer for 24 h to 36 h. The freeze drying temperature is -40 ° C to -42 ° C, so that the sample is completely dried to obtain the intermediate.

[0040] (3) The intermediate was transferred to a tubular furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating treatment. The obtained sample was labeled PC@Co(PO3)2-3.

[0041] (4) BC@Co(PO3)2-3, acetylene black and PVDF were mixed and ground in a mass ratio of 8:1:1. During the grinding process, NMP was added in an appropriate amount until it was ground into a uniform slurry. The slurry was scraped onto a copper foil using a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-3 electrode.

[0042] Example 4

[0043] (1) Take 57.6 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; disperse 0.9 mg of bacterial cellulose in deionized water to form a bacterial cellulose dispersion with a mass percentage of 80%; mix the graphite oxide dispersion and the bacterial cellulose dispersion to form a gel; add 0.58 g of phytic acid to the gel; finally, add 73 mg of Co(NO3)2 to the mixed solution and fully dissolve and shake to obtain a precursor solution.

[0044] (2) The precursor solution is transferred to an insulated box and pre-frozen with liquid nitrogen until the sample is completely frozen. The sample is then placed in a freeze dryer and dried for 24 h to 36 h at a freeze drying temperature of -42 °C to -45 °C to completely dry the sample to obtain the intermediate.

[0045] (3) The intermediate was transferred to a tubular furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating treatment. The obtained sample was labeled PC@Co(PO3)2-4.

[0046] (4) PC@Co(PO3)2-4, acetylene black and PVDF were mixed and ground in a mass ratio of 8:1:1. NMP was added in an appropriate amount during the grinding process until it was ground into a uniform slurry. The slurry was scraped onto copper foil using a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-4 electrode.

[0047] Comparative Example 1

[0048] (1) Take 51.2 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; disperse 1.8 mg of bacterial cellulose in deionized water to form a bacterial cellulose dispersion with a mass percentage of 80%; mix the graphite oxide dispersion and the bacterial cellulose dispersion to form a gel; add 0.58 g of hydroxyethylidene diphosphonic acid to the gel; finally, add 73 mg of Co(NO3)2 to the mixed solution and fully dissolve and shake to obtain a precursor solution.

[0049] (2) The precursor solution is transferred to an insulated box and pre-frozen with liquid nitrogen until the sample is completely frozen. The sample is then placed in a freeze dryer and dried for 24 h to 36 h at a freeze drying temperature of -40 °C to -42 °C to completely dry the sample and obtain the intermediate.

[0050] (3) The intermediate was transferred to a tube furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating treatment. The obtained sample was labeled PC@Co(PO3)2-EA.

[0051] (4) PC@Co(PO3)2-EA, acetylene black and PVDF were mixed and ground in a mass ratio of 8:1:1. NMP was added in an appropriate amount during the grinding process until it was ground into a uniform slurry. The slurry was scraped onto a copper foil using a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-EA electrode.

[0052] Comparative Example 2

[0053] (1) Take 51.2 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; disperse 1.8 mg of bacterial cellulose in deionized water to form a bacterial cellulose dispersion with a mass percentage of 80%; mix the graphite oxide dispersion and the bacterial cellulose dispersion to form a gel; add 0.58 g of phenylphosphonic acid to the gel; finally, add 73 mg of Co(NO3)2 to the mixed solution and fully dissolve and shake to obtain a precursor solution.

[0054] (2) The precursor solution is transferred to an insulated box and pre-frozen with liquid nitrogen until the sample is completely frozen. The sample is then placed in a freeze dryer and dried for 24 h to 36 h at a freeze drying temperature of -40 °C to -42 °C to completely dry the sample and obtain the intermediate.

[0055] (3) The intermediate was transferred to a tube furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating treatment. The obtained sample was labeled PC@Co(PO3)2-PC.

[0056] (4) PC@Co(PO3)2-PC, acetylene black and PVDF were mixed and ground in a mass ratio of 8:1:1. During the grinding process, NMP was added in an appropriate amount until it was ground into a uniform slurry. The slurry was scraped onto copper foil using a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-PC electrode.

[0057] Comparative Example 3

[0058] (1) Take 51.2 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; 1.8 mg of bacterial cellulose is dispersed in deionized water to form a bacterial cellulose dispersion with a mass percentage of 80%; the graphite oxide dispersion and the bacterial cellulose dispersion are mixed evenly to form a gel; finally, 73 mg of Co(NO3)2 is added to the mixed solution and fully dissolved and shaken to obtain a precursor solution.

[0059] (2) The precursor solution is transferred to an insulated box and pre-frozen with liquid nitrogen until the sample is completely frozen. The sample is then placed in a freeze dryer and dried for 24 h to 36 h at a freeze drying temperature of -40 °C to -42 °C to completely dry the sample and obtain the intermediate.

[0060] (3) The intermediate was transferred to a tube furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating treatment. The obtained sample was labeled PC@Co(PO3)2-NO.

[0061] (4) PC@Co(PO3)2-NO, acetylene black and PVDF were mixed and ground in a mass ratio of 8:1:1. During the grinding process, NMP was added in an appropriate amount until it was ground into a uniform slurry. The slurry was scraped onto copper foil using a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-NO electrode.

[0062] Comparative Example 4

[0063] (1) Take 51.2 mg of graphite oxide and disperse it in deionized water to form a graphite oxide dispersion with a concentration of 6.4 mg / mL; 1.8 mg of nanocellulose is dispersed in deionized water to form a nanocellulose dispersion with a mass percentage of 80%; the graphite oxide dispersion and the bacterial cellulose dispersion are mixed evenly to form a gel; after mixing evenly, 0.58 g of phytic acid is added; finally, 73 mg of Co(NO3)2 is added to the mixed solution and fully dissolved and shaken to obtain a precursor solution.

[0064] (2) The precursor solution is transferred to an insulated box and pre-frozen with liquid nitrogen until the sample is completely frozen. The sample is then placed in a freeze dryer and dried for 24 h to 36 h at a freeze drying temperature of -40 °C to -42 °C to completely dry the sample and obtain the intermediate.

[0065] (3) The intermediate was transferred to a tube furnace and kept at 300 °C for 30 min under an argon atmosphere, and then kept at 900 °C for 2 h for high-temperature carbonization and phosphating treatment. The obtained sample was labeled PC@Co(PO3)2-LC.

[0066] (4) PC@Co(PO3)2-LC, acetylene black and PVDF were mixed and ground in a mass ratio of 8:1:1. NMP was added in an appropriate amount during the grinding process until it was ground into a uniform slurry. The slurry was scraped onto copper foil using a 50 μm scraper and vacuum dried for more than 8 h. The dried electrode was taken out and placed on the tablet press to punch out a 14 mm PC@Co(PO3)2-LC electrode.

[0067] Comparative Example 5

[0068] The difference from the embodiment is that pure copper foil is placed at the mouth of the tablet press and punched into 14 mm pole pieces for assembling Li / / Cu half-cells and Li / / Li pair cells.

[0069] In order to further illustrate the effect of the embodiment of the present invention, the composite lithium negative electrode prepared in the embodiment, comparative examples 1-4 and the pure copper in comparative example 5 are used as electrodes to assemble corresponding Li / / Cu half-cells and Li / / Li counter-cells, and the test process is as follows:

[0070] (1) The composite negative electrodes prepared in Examples and Comparative Examples 1-4 and the pure copper foil in Comparative Example 5 were paired with commercial lithium sheets, polypropylene was used as a separator, and a Li / / Cu half-cell was assembled in a glove box with a water and oxygen content of less than 0.1 ppm to test the deposition and stripping efficiency of Li in the electrode. The electrolyte solute was lithium trifluoromethylsulfonyl imide (LiTFSI), the solvent was 1,3-dioxolane (DOL) and dimethoxymethane (DME) in a volume ratio of 1:1, the additive was 0.1 mol / L LiNO3, the electrolyte concentration was 1 mol / L, and the amount was 60 µL.

[0071] (2) First, the Li / / Cu half-cells of Example 3 and Comparative Example 5 with the best electrochemical performance were assembled and tested at 0.5 mA cm -2 At a current density of 10 mAh cm -2 of lithium metal. Then, the Li / / Cu half-cell was disassembled in a glove box with a water and oxygen content of less than 0.1ppm, the electrode after lithium insertion was taken out, and the Li / / Li pair battery was assembled with polypropylene as the separator. The electrolyte solute was lithium trifluoromethylsulfonyl imide (LiTFSI), the solvent was 1,3-dioxolane (DOL) and dimethoxymethane (DME) in a volume ratio of 1:1, the additive was 0.1 mol / L LiNO3, the electrolyte concentration was 1 mol / L, and the amount was 60 µL.

[0072] 1. Example Li / / Cu half-cell cycle number-Coulombic efficiency test analysis

[0073] In a Li / / Cu half-cell, the higher the Coulombic efficiency, the better the reversibility of lithium deposition / stripping in the negative electrode during the cycle, and the more stable the negative electrode. Figure 1 The coulombic efficiency of the Li / / Cu half-cell after the composite lithium negative electrode in Example 1, Example 2, Example 3, and Example 4 is compared with that of the pure copper negative electrode and metallic lithium in Comparative Example 5. It can be seen from the figure that at a current density of 1.0 mA·cm -2Under the test conditions, the first cycle coulombic efficiency of the Li||PC@Co(PO3)2-3 half-cell in Example 3 is the highest. After about 10 cycles, the coulombic efficiency of the Li||PC@Co(PO3)2-3 half-cell is the highest and can maintain more than 90% for 40 stable cycles. Although it decays slightly thereafter, it still remains above 80%. In comparison, the coulombic efficiency of the Li / / Cu half-cell assembled with the composite lithium negative electrode in Example 1, Example 2, and Example 4 is low and fluctuates greatly during the cycle. After about 20-40 cycles of decay, they all show rapid decay of coulombic efficiency. The coulombic efficiency fluctuation of the Li / / Cu half-cell assembled with the pure copper negative electrode in Comparative Example 5 is more obvious during the initial cycle, showing worse cycle stability. In summary, the data of Examples 1 to 4 all perform better than those of Comparative Example 5, among which the PC@Co(PO3)2 carrier material in Example 3 is the most prominent. The above results show that the PC@Co(PO3)2 carrier material in Example 3 can effectively regulate the process of lithium metal negative electrode deintercalation and extraction during charging and discharging, alleviate the uncontrollable growth of lithium dendrites and the volume expansion of lithium during charging and discharging.

[0074] 2. Example Li / / Cu half-cell capacity-voltage curve analysis

[0075] In the capacity-voltage curve of the Li / / Cu half-cell, the smaller the nucleation overpotential, the better the lithium affinity of the negative electrode carrier material, and the more helpful it is to inhibit the growth of lithium dendrites. Therefore, in order to evaluate the affinity of the composite carrier materials in Examples 1, 2, 3, and 4 and the pure copper negative electrode in Comparative Example 5 with lithium, the Li / / Cu half-cell assembled with the above composite negative electrode was tested for capacity-voltage analysis. The results are as follows: Figure 2 As shown in the figure, during the initial lithium deposition process, the discharge curve shows an obvious voltage drop, and then forms a flat voltage platform. The difference between the lowest voltage of the voltage drop and the platform voltage is the nucleation overpotential of lithium metal. The capacity-voltage curves of the five half-cells are shown in Table 1.

[0076] Table 1 1.0 mA·cm -2 Minimum voltage and nucleation overpotential of different composite anodes under different conditions

[0077]

[0078] It can be seen that the nucleation overpotential of the Cu foil in Comparative Example 5 is the highest, reaching 14.6 mV, while the nucleation overpotential of the Li / / Cu half-cell assembled by the composite negative electrode in Example 3 is the lowest, about 11.8 mV, indicating that PC@Co(PO3)2-3 has good affinity with lithium and a faster lithium ion migration rate, and can even out the lithium ion flux during the cycle, inducing uniform deposition of lithium, thereby reducing its nucleation energy barrier.

[0079] 3. Comparative Example Li / / Cu Half-Cell Cycle Number-Coulombic Efficiency Test Analysis

[0080] In order to further demonstrate the feasibility of Example 3, comparative examples 1-4 were prepared by changing the phosphorus source or carbon source, and the four comparative example composite negative electrodes were paired with metallic lithium to assemble Li / / Cu half-cells. Figure 3 The coulombic efficiency of the Li / / Cu half-cell assembled with the composite lithium negative electrode in Comparative Examples 1-4 and Example 3 is compared. It can be seen from the figure that at a current density of 1.0 mA cm -2 Under the test conditions, the coulombic efficiency of the Li / / Cu half-cell assembled with the composite lithium negative electrode in Comparative Examples 1-4 was relatively stable during the initial cycle, but the coulombic efficiency quickly decayed after 20-40 cycles. In contrast, although the coulombic efficiency of the Li||PC@Co(PO3)2-3 half-cell in Example 3 fluctuated during the cycle and decayed after 40 cycles, it was still maintained at more than 80%. The above results show that after changing the phosphorus source or carbon source, the prepared carrier material has a weakened regulating effect on the lithium metal negative electrode's lithium insertion and extraction process during the charging and discharging process, and has no obvious improvement effect on alleviating the uncontrollable growth of lithium dendrites and the volume expansion of lithium during the charging and discharging process.

[0081] 4. Analysis of time-voltage curves of negative electrode assembled Li / / Li symmetric cells in Example 3 and Comparative Example 5

[0082] In order to further evaluate the stability of the composite lithium negative electrode during the cycle and the ability to inhibit the growth of lithium dendrites, the best performance of Example 3 was selected to assemble a Li / / Li symmetric battery and test its long-term cycle stability. Figure 4 3 and 5 are time-voltage curves of the Li / / Li symmetrical battery assembled with negative electrodes in Example 3 and Comparative Example 5. Figure 4 As shown in a, at 3 mA·cm -2 When cycling at the current density of 1.5 Å, the Li / / Li symmetrical battery assembled by Comparative Example 5 showed obvious voltage changes after cycling for about 80 h, and its voltage rapidly increased to about 0.6 V and fluctuated violently, while the Li / / Li battery assembled with the Li@PC@Co(PO3)2-3 composite lithium negative electrode of Example 3 could stably cycle for more than 220 h. Figure 4As shown in the partial enlarged image of b, at 3 mA·cm -2 At the current density, the Li / / Li symmetric battery in Comparative Example 5 exhibits a large polarization voltage (144 mV), while the polarization voltage in Example 3 is only 79 mV. The above results show that the PC@Co(PO3)2-3 composite negative electrode of Example 3 can remain stable during the cycle and guide the uniform deposition of lithium, thereby reducing the polarization voltage.

[0083] 5. XRD pattern analysis of the composite materials in Example 3 and Comparative Examples 1-4

[0084] Figure 5 The XRD spectra of the carrier materials of Example 3 and Comparative Examples 1-4 are shown in the test range of 10° to 80°. Figure 5 It can be seen from a that the material in Example 3 has three characteristic peaks of Co(PO3)2 at 2θ≈14.4°, 2θ≈20.8° and 2θ≈29.7°, proving that the negatively charged phosphate groups in phytic acid react with cobalt nitrate to generate Co(PO3)2 during the high-temperature phosphating process. Figure 5 As shown in Figure 2, no characteristic peaks were observed in the XRD spectra of Comparative Examples 1 and 2 using hydroxyethylidene diphosphonic acid and phenylphosphonic acid as phosphorus sources, which may be due to the fact that these two organic phosphorus sources are difficult to react with cobalt nitrate or that cobalt exists in the form of a single atom. In contrast, in Comparative Example 3, no phosphorus source was added, and only the peak of elemental cobalt was observed in the material, while the characteristic peak of CoP was observed in the XRD of the carrier material of Comparative Example 5, indicating that the phosphate group in phytic acid decomposed at high temperature and reacted with cobalt nitrate to generate CoP.

[0085] 6. SEM image analysis of the material in Example 3

[0086] The material prepared in Example 3 was taken and subjected to SEM characterization analysis. Figure 6 The SEM images of Example 3 obtained at different magnifications show that the surface of the material after phosphating is slightly rough and uneven at low magnifications ( Figure 6 a). After magnification, it was observed that the surface of the material showed a wrinkled morphology of graphite oxide accumulation, and there were pores between these wrinkles. Therefore, the material as an electrode is conducive to the diffusion of electrolyte, the migration of lithium ions, and provides sites for the uniform deposition of lithium dendrites ( Figure 6 bc). However, the fiber structure of bacterial cellulose was not clearly observed in the image, which may be because the diameter of the bacterial cellulose fiber used was about 100-150 nm, and the magnification used this time was too low to observe the specific fiber structure.

[0087] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite lithium metal negative electrode carrier material, characterized in that: The following steps are involved: Dispersing graphite oxide and bacterial cellulose respectively to obtain graphite oxide dispersion and bacterial cellulose dispersion, mixing the two to obtain a gel, wherein the mass ratio of graphite oxide to bacterial cellulose is 38-58:0.8-3.8; After adding phytic acid to the gel, a cobalt nitrate hexahydrate solution is added thereto to react and obtain a precursor solution, wherein the mass ratio of phytic acid to graphite oxide is 580-585:38-58, and the mass ratio of cobalt nitrate hexahydrate to graphite oxide is 71-75:38-58; freeze-drying the precursor solution to obtain an intermediate; The intermediate was first calcined at 280-310°C for 25-35 min and then calcined at 880-930°C for 1.8-2.2 h in an inert gas atmosphere to obtain a PC@Co(PO3)2 composite material.

2. The method for preparing a composite lithium metal negative electrode carrier material according to claim 1, characterized in that: The mass ratio of the graphite oxide to the bacterial cellulose is 51.2:1.8; the mass ratio of the phytic acid to the graphite oxide is 580:51.2; and the mass ratio of the cobalt nitrate hexahydrate to the graphite oxide is 73:51.

2.

3. The method for preparing the composite lithium metal negative electrode carrier material according to claim 1, characterized in that: The freeze-drying temperature is -40°C to -50°C.

4. The method for preparing a composite lithium metal negative electrode carrier material according to claim 1, characterized in that: The inert gas is argon.

5. The method for preparing a composite lithium metal negative electrode carrier material according to claim 1, characterized in that: The intermediate was first calcined at 300°C for 30 min and then at 900°C for 2 h in an inert gas atmosphere to obtain a PC@Co(PO3)2 composite material.

6. The method for preparing a composite lithium metal negative electrode carrier material according to claim 1, characterized in that: The concentration of graphite oxide in the graphite oxide dispersion is 6.0-7.0 mg / mL; The mass percentage of bacterial fibers in the bacterial cellulose dispersion is 75-85%.

7. The method for preparing a composite lithium metal negative electrode carrier material according to claim 1, characterized in that: The intermediate is coated with copper foil and then calcined.

8. A composite lithium metal negative electrode carrier material obtained by the preparation method according to any one of claims 1 to 7.

9. A lithium-sulfur battery, characterized in that: The negative electrode material of the lithium-sulfur battery is mainly made of the composite lithium metal negative electrode carrier material as claimed in claim 8, a binder and a conductive agent.

10. The lithium-sulfur battery according to claim 9, characterized in that: The negative electrode material is coated on a copper foil to form a negative electrode sheet, and the coating thickness of the negative electrode material on the copper foil is 45-55 μm.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen-doped carbon fiber / nitrogen-doped graphene / bacterial cellulose membrane material

    CN105355450A

  • Nitrogen doping carbonized bacterial cellulose / graphene / platinum composite nanomaterial and preparation method thereof

    CN106410223A